Quality of life assessment in stoma patients in a tertiary care hospital in South India: a cross- sectional study - Roshini, A. P.; Sunny, Ann; Rozario, Anthony P. (International Surgery Journal, 2017)
Background: Quality of life (QOL) of patients is affected due to procedures done to treat the disease. A good QOL is essential to achieve a holistic approach in treating patients. Methods: We did a cross-sectional study in a tertiary care hospital to describe, identify and compare the factors affecting the QOL of these patients. Results: 42.5% had a permanent stoma and a majority 32.5% were due to a malignancy. Major concerns were skin rash and irritation, depression, loneliness and suicidal thoughts. 62.5% of the total had not gone to work after creation of a stoma. Malignancy was found to be a significant predictor of having a low QOL score. Conclusions: Quality of life of stoma patients in present study was not ideal. There is a definite need to have support groups for these patients in all hospitals.